DIGITAL LEADERSHIP AND CYBERSECURITY GOVERNANCE IN SECONDARY SCHOOLS: A COMPARATIVE STUDY OF PUBLIC AND PRIVATE INSTITUTIONS (Qualitative Research Journal for Social Studies, 2026)
This study explored how digital leadership affects cybersecurity governance in public and private secondary schools in the punjab. The researchers also examined whether school type, gender, and administrative experience influenced this relationship. A total of 120 school leaders and teachers participated in the study using surveys on digital leadership and cybersecurity governance. The findings showed a strong positive relationship between digital leadership and cybersecurity governance. This means that schools with better digital leadership also had stronger cybersecurity practices. Digital leadership explained 47% of the improvement in cybersecurity governance. The study also found that private schools had better cybersecurity governance than public schools. In addition, school type, gender, and administrative experience had significant effects on the relationship between digital leadership and cybersecurity governance. Overall, the study highlights that strong digital leadership is important for improving cybersecurity, developing effective policies, and creating a safer digital environment in schools.